(3GdJPcQI aj GdbQGAGJs - (3CHh GdMSf WGgQ Hf YHO GdefYe Hf ZdHhfs; (3YHO GdQMef Hf CMeO Hf eSYhO GdchGcHj, GdSjO GdaQGJj,J (B1320 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf CeG HYO MeO Gddg HLejY eMGeOg aEfi PGcQ ai gPG GdcJGH eG JCQi Edi ef bQGAI CFeI GdCeUGQi GdeTghQjf HGdEjLGR s
(3BNQgG (B:s
(3aGdMed Ydi eG QSeJ dc fUH GdUhGH hJQTO Ef TGA Gddg YR hLd s
(3GdfSNI HChdgG bQGAI SfI (B602s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B298 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B115s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs